Two-component RTV adhesive sealing silicone rubber and preparation method thereof
By adjusting the formulation of two-component RTV bonding sealing silicone rubber and adding modified fillers and specific catalysts, the problem of insufficient mechanical properties is solved, and the mechanical strength, wear resistance and bonding properties are significantly improved.
Patent Information
- Application Number
- CN202411403299.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The mechanical properties of two-component RTV bonding sealing silicone rubber are relatively lacking and it is difficult to meet certain high-demand application scenarios.
By adjusting the formulation of components A and B, dimethyl silicone oil, modified filler and chelating tin catalyst were added, as well as 107 silicone rubber, modified filler, crosslinker and silane coupling agent respectively, the mechanical strength, wear resistance and adhesive properties of the silicone rubber were improved.
The mechanical strength, hardness, wear resistance and bonding properties of two-component RTV bonding sealed silicone rubber are significantly improved, and their performance in high demanding applications are improved.
Smart Images

Figure BDA0005075842090000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sealants, and more specifically, to a two-component RTV bonding and sealing silicone rubber and a preparation method thereof. Background Art
[0002] Two-component RTV adhesive sealing silicone rubber is a special type of silicone rubber, usually composed of component A and component B. After mixing, it needs to be cured to obtain silicone rubber with good tolerance, adhesion and ease of use. It is usually used for bonding, sealing, waterproofing and protecting various components. It is commonly used in electronics, automobiles, construction, aerospace and other fields, such as making sealing gaskets, waterproof coatings or as structural adhesives.
[0003] The two-component RTV adhesive sealing silicone rubber raw material is based on hydroxyl-terminated polydimethylsiloxane as the base resin, combined with cross-linking agents, coupling agents, catalysts, fillers, etc. It has excellent properties such as high and low temperature resistance, weather resistance, and vibration reduction, but its overall mechanical properties are still far from ideal. Summary of the invention
[0004] In order to improve the problem of poor mechanical properties of two-component RTV adhesive sealing silicone rubber, the present application provides a two-component RTV adhesive sealing silicone rubber and a preparation method thereof.
[0005] In the first aspect, the present application provides a two-component RTV adhesive sealing silicone rubber, which adopts the following technical scheme: a two-component RTV adhesive sealing silicone rubber, comprising component A and component B, characterized in that the component A comprises the following raw materials in parts by weight: 100 parts of dimethyl silicone oil, 15-25 parts of modified filler, and 1-2 parts of chelated tin catalyst; the component B comprises the following raw materials in parts by weight: 100 parts of 107 silicone rubber, 10-20 parts of modified filler, 3-5 parts of crosslinking agent, and 2-3 parts of silane coupling agent;
[0006] The modified filler comprises the following raw materials: 10-15 parts of modified white carbon black, 5-8 parts of nano calcium carbonate, 7-12 parts of modified clay and 2-5 parts of talc.
[0007] By adopting the above technical solution, in component A, dimethyl silicone oil has good lubricity and can adjust the fluidity of the system, making it easier to mix components A and B, and easier to seal or bond to the surface of the object during the subsequent two-component RTV adhesive sealing silicone rubber construction, and has high mechanical strength; dimethyl silicone oil can also control the curing speed, so that the processing time can be accurate, and can also increase the flexibility and elongation of the cured silicone rubber, and improve the adaptability and sealing performance of the system. The modified filler can increase the hardness, mechanical strength and wear resistance of the system, improve the structural stability of the cured system, and adjust the viscosity of the system, making the silicone rubber easier to apply, further improving the adhesion of the silicone rubber to the substrate, and improving the sealing effect. The chelated tin catalyst can promote the cross-linking and curing of silicone rubber, so that the silicone rubber can quickly reach sufficient curing strength at room temperature.
[0008] In component B, 107 silicone rubber has good temperature resistance, elasticity, sealing and chemical stability, and forms a three-dimensional network structure with the cross-linking agent, which transforms the liquid into a solid state and solidifies into a solid elastomer. The silane coupling agent further increases the adhesion of the system, improves the durability of the system and the interface compatibility. The modified filler also increases the hardness, viscosity, mechanical strength and wear resistance of the system, and improves the structural stability of the system after curing.
[0009] Among the modified fillers, modified silica can improve the hardness, tensile strength, tear strength and wear resistance of silicone rubber, so that it has better mechanical properties after curing. It can also increase the contact area between silicone rubber and the substrate, improve the bonding effect, and adjust the consistency of the silicone rubber mixture so that it has good thixotropy during sizing. It also helps to improve the thermal stability and chemical stability of silicone rubber and prevent volume shrinkage during or after curing. Nano-calcium carbonate increases the filling effect of silicone rubber, improves the hardness, modulus and compression deformation resistance of the system, and modified clay can increase the volume of silicone rubber and improve the density and hardness of the material. Nano-calcium carbonate can be loaded on the surface of modified silica and in the pores of modified clay to improve the adhesion between silicone rubber and the substrate, improve the sealing effect and stability, and improve the tensile strength and wear resistance of silicone rubber. Talc can also be filled on the surface of modified silica and in the pores of modified clay to improve the hardness, tensile strength and tear resistance of silicone rubber and the heat resistance of silicone rubber. The various components in the modified filler cooperate with each other to jointly improve the mechanical properties of silicone rubber.
[0010] Optionally, the modified filler includes, in parts by weight: 10-15 parts of modified white carbon black, 5-8 parts of nano calcium carbonate, 7-12 parts of modified clay, and 2-5 parts of talc.
[0011] By adopting the above technical scheme, the dosage ratio of each component is further limited, and each component has the mechanical properties of oil within a certain dosage range. Modified white carbon black can improve the hardness, tensile strength, tear strength and wear resistance of silicone rubber, nano calcium carbonate increases the hardness, modulus and compression deformation resistance of silicone rubber, modified clay can increase the volume of silicone rubber, improve the density and hardness of the material, talcum powder increases the hardness, tensile strength and tear resistance of silicone rubber, and various components cooperate with each other to jointly improve the mechanical properties of silicone rubber.
[0012] Optionally, the preparation method of the modified silica comprises the following steps:
[0013] (1) grinding white carbon black, dispersing it in a silane coupling agent aqueous solution, adding acetic acid, stirring for 1-2 hours, washing with water, filtering, and obtaining pretreated white carbon black;
[0014] (2) Dispersing the modified graphene in deionized water, adding the pretreated white carbon black in step (1), stirring at a temperature of 80-85° C. for 1-2 h, filtering, then spraying the chitosan solution, dispersing evenly, drying, and grinding to obtain modified white carbon black.
[0015] By adopting the above technical solution, white carbon black is easy to agglomerate, and the silane coupling agent modifies the white carbon black to reduce the surface energy of the white carbon black. Moreover, the silane coupling agent, as an interfacial agent, can bridge the chemical differences between the white carbon black and the matrix resin, and improve the adhesion between the two by forming chemical bonds, thereby improving the overall bonding strength of the material.
[0016] The modified graphene has high strength and high elasticity, and can be loaded on the surface or in the pores of silica to improve the tensile strength, elongation at break and wear resistance of silica. It can be subsequently used in silicone rubber to improve the mechanical properties, weather resistance and service life of silicone rubber, improve the fluidity and thixotropy of the silicone rubber mixture, make it easier to apply glue, and maintain its shape after curing; the chitosan solution is sprayed on the surface of silica to make the bonding between the modified graphene and silica more stable, and the chitosan can also cross-link with silicone rubber to improve the mechanical strength of silicone rubber. The modified silica has better mechanical properties, wear resistance and stability, which can further improve the corresponding performance of silicone rubber.
[0017] Optionally, the mass ratio of the white carbon black, the modified graphene and the chitosan solution is 1:0.1-0.3:0.5-0.7.
[0018] By adopting the above technical scheme, the mass ratio of silica, modified graphene and chitosan solution is further limited within a certain range, so as to improve the mechanical properties of silica. There is a synergistic effect between silica, modified graphene and chitosan solution. The modified graphene is loaded on the surface and pores of silica. The chitosan solution makes silica and modified graphene adhere tightly. The modified silica has good tensile strength, elongation at break and wear resistance. The subsequent application in silicone rubber also improves the adhesion and durability of silicone rubber.
[0019] Optionally, the preparation method of the modified graphene comprises the following steps: adding hydrogen peroxide and concentrated hydrochloric acid to the graphene, stirring evenly, reacting for 1-1.5 hours, washing with water to obtain hydroxyl-modified graphene, and then dispersing it in deionized water, adding nano-silicon dioxide and sodium dodecylbenzene sulfonate, stirring for 1-2 hours, filtering, and drying to obtain modified graphene.
[0020] By adopting the above technical scheme, graphene, hydrogen peroxide and concentrated hydrochloric acid are first reacted to obtain hydroxyl-modified graphene. Nano-silicon dioxide has high mechanical strength and wear resistance and can be loaded on the surface of graphene to improve the tensile strength, hardness and toughness of graphene. Subsequently, the mechanical strengths such as tensile strength, tear strength and wear resistance of silicone rubber can be improved, and the adhesion between silicone rubber and substrate can be increased to improve the sealing effect. Sodium dodecylbenzene sulfonate is used as a surface modifier to help graphene and nano-silicon dioxide disperse in the solution, prevent agglomeration, improve the uniformity of the solution, and thus improve the mechanical properties and stability of the modified graphene.
[0021] Optionally, the method for preparing the modified clay comprises the following steps:
[0022] (1) grinding clay, dispersing it in a sodium hydroxide solution and soaking it for 2-3 hours, washing it with water, and then dispersing it in deionized water, adding boric acid, stirring it evenly, and filtering it to obtain pretreated ceramsite;
[0023] (2) dispersing the pretreated ceramsite of step (1) in anhydrous ethanol, adding modified glass fiber and carnauba wax, stirring at a temperature of 80-85° C. for 3-5 minutes, dispersing evenly, drying, and grinding to obtain modified clay.
[0024] By adopting the above technical scheme, the sodium hydroxide solution erodes the clay surface to a certain extent, thereby increasing the specific surface area of the clay and removing organic impurities in the clay. Boric acid releases exchangeable boron ions, which exchange ions with cations on the surface of clay particles, thereby improving the charge balance and adsorption performance of the clay and enhancing the bonding performance of the clay mixture.
[0025] The modified glass fiber has good heat resistance and high strength. It can be loaded on the surface of ceramsite to improve the mechanical strength, toughness and wear resistance of ceramsite and reduce the shrinkage and cracking of ceramsite during the drying process. After the carnaba wax is dissolved, it can cover the pretreated ceramsite, so that the modified glass fiber and ceramsite are tightly bonded, which improves the performance stability of the modified clay. It is subsequently used in silicone rubber to make the various components in the silicone rubber mixed evenly, thereby improving the performance stability of the silicone rubber.
[0026] Optionally, the mass ratio of the clay, modified glass fiber and carnauba wax is 1:0.3-0.5:0.07-0.09.
[0027] By adopting the above technical scheme, the mass ratio of clay, modified glass fiber and carnauba wax is further limited within a certain range, thereby improving the mechanical strength of the clay. The modified glass fiber has good heat resistance and high strength and can be loaded on the surface of ceramsite to improve the mechanical strength, toughness and wear resistance of the ceramsite. After being dissolved, the carnauba wax can coat the pretreated ceramsite, so that the modified glass fiber and ceramsite are tightly bonded, thereby improving the performance stability of the modified clay. The carnauba wax also helps to adjust the consistency of the silicone rubber, improve its fluidity during processing, make the material easier to disperse evenly, and thus improve the corresponding performance of the silicone rubber.
[0028] Preferably, the preparation method of the modified glass fiber comprises the following steps: ultrasonically crushing the glass fiber for 15-20 minutes, dispersing it in a dilute sulfuric acid solution, washing it with water, mixing it evenly with sodium dibutylnaphthalene sulfonate and pearlescent powder, and drying it to obtain the modified glass fiber.
[0029] By adopting the above technical scheme, the glass fiber is first crushed, and the surface of the glass fiber is treated with dilute sulfuric acid to remove organic impurities on the surface of the glass fiber. Sodium dibutylnaphthalene sulfonate is attached to the glass fiber as a surface modifier to change the surface properties of the glass fiber and increase the dispersibility of the glass fiber in the liquid. Pearlescent powder can be loaded on the surface of the glass fiber to increase the strength, toughness and durability of the glass fiber. It is subsequently applied to modified clay to improve the corresponding properties of the clay, and finally applied to silicone rubber to improve the oxidation resistance and durability of silicone rubber, while adjusting the rheology, curing speed and hardness of silicone rubber.
[0030] Preferably, the preparation method of the modified filler comprises the following steps: dispersing modified silica in deionized water, stirring at a temperature of 60-65° C. for 20-25 min, adding nano calcium carbonate, modified clay, and talcum powder, continuing stirring for 1-2 h, grinding, and drying to obtain the modified filler.
[0031] By adopting the above technical solution, the modified filler obtained by uniformly mixing various components has better mechanical properties. The various components are uniformly mixed and subsequently jointly improve the mechanical properties and adhesion of the silicone rubber.
[0032] In a second aspect, the present application provides a method for preparing a two-component RTV adhesive sealing silicone rubber, comprising the following steps: stirring dimethyl silicone oil and modified filler at a vacuum degree of -0.1-0.1 MPa at a speed of 900-1000 rpm for 30-35 min, adding a chelated tin catalyst and continuing stirring for 1-1.5 h to obtain component A;
[0033] Stir 107 silicone rubber and modified filler at a vacuum degree of -0.1-0.1 MPa at a speed of 1100-1200 rpm for 20-30 min, add a crosslinking agent and a silane coupling agent and continue stirring for 1-1.5 hours to obtain component B;
[0034] Mix component A and component B in a mass ratio of 5-10:1 and cure to obtain the product.
[0035] By adopting the above technical scheme, the present application mixes the various raw material components, the production process is simple, the preparation efficiency is high, and a two-component RTV bonding and sealing silicone rubber with excellent performance in all aspects is obtained, thereby improving the application of the two-component RTV bonding and sealing silicone rubber.
[0036] In summary, this application has the following beneficial effects:
[0037] 1. In the component A of the present application, dimethyl silicone oil has good lubricity and can adjust the fluidity of the system, making it easier to mix the components A and B, making it easier to seal or bond to the surface of an object during the subsequent two-component RTV adhesive sealing silicone rubber construction, and having higher mechanical strength.
[0038] 2. In component B of this application, 107 silicone rubber has good temperature resistance, elasticity, sealing and chemical stability, and forms a three-dimensional network structure with the cross-linking agent, so that the liquid is transformed into a solid state and solidified into a solid elastomer. The silane coupling agent further increases the adhesion of the system and improves the durability and interface compatibility of the system.
[0039] 3. Among the modified fillers in this application, the modified silica can improve the hardness, tensile strength, tear strength and wear resistance of the silicone rubber, so that it has better mechanical properties after curing, and can also increase the contact area between the silicone rubber and the substrate, thereby improving the bonding effect. DETAILED DESCRIPTION
[0040] Preparation example of modified silica
[0041] Preparation Example 1-1
[0042] The preparation method of modified white carbon black comprises the following steps:
[0043] (1) Grind 1.2 kg of white carbon black, then disperse it in 2 L of 0.2% mass concentration of silane coupling agent A171 aqueous solution, add 0.2 L of 10% mass fraction of acetic acid, stir for 2 h, wash with water, and filter to obtain pretreated white carbon black;
[0044] (2) Dispersing the modified graphene in 1 L of deionized water, adding the pretreated white carbon black in step (1), stirring at a temperature of 85° C. for 2 h, filtering, then spraying the chitosan solution, dispersing evenly, drying, and grinding to obtain modified white carbon black.
[0045] The mass ratio of white carbon black, modified graphene and chitosan solution is 1:0.1:0.5.
[0046] The preparation method of modified graphene comprises the following steps: adding 1L of hydrogen peroxide and 0.5L of concentrated hydrochloric acid with a mass concentration of 36% to 0.3kg of graphene, stirring evenly, reacting for 1.5h, washing with water to obtain hydroxyl-modified graphene, then dispersing in 1.2L of deionized water, adding 0.3kg of nano-silicon dioxide and 0.2kg of sodium dodecylbenzene sulfonate, stirring for 1-2h, filtering, and drying to obtain modified graphene.
[0047] Preparation Example 1-2
[0048] The difference from Preparation Example 1-1 is that in step (2), no modified graphene is added.
[0049] Preparation Example 1-3
[0050] The difference from Preparation Example 1-1 is that in step (2), the chitosan solution is not sprayed.
[0051] Preparation Example 1-4
[0052] The difference from Preparation Example 1-1 is that the mass ratio of white carbon black, modified graphene and chitosan solution is 1:0.3:0.7.
[0053] Preparation Example 1-5
[0054] The difference from Preparation Example 1-1 is that the mass ratio of white carbon black, modified graphene and chitosan solution is 1:0.8:0.1.
[0055] Preparation Example 1-6
[0056] The difference from Preparation Example 1-1 is that no nano-silicon dioxide is added in the preparation method of modified graphene.
[0057] Preparation Example 1-7
[0058] The difference from Preparation Example 1-1 is that sodium dodecylbenzene sulfonate is not added in the preparation method of modified graphene.
[0059] Preparation example of modified clay
[0060] Preparation Example 2-1
[0061] The preparation method of modified pottery clay comprises the following steps:
[0062] (1) 1.3 kg of clay was ground, dispersed in 2 L of 6% sodium hydroxide solution, soaked for 3 h, washed with water, and then dispersed in 2.5 L of deionized water, 0.2 kg of boric acid was added, stirred evenly, and filtered to obtain pretreated ceramsite;
[0063] (2) The pretreated ceramsite of step (1) is dispersed in 2.5 L of anhydrous ethanol, and modified glass fiber and carnauba wax are added, stirred at a temperature of 85° C. for 5 min, uniformly dispersed, dried, and ground to obtain modified clay.
[0064] The mass ratio of clay, modified glass fiber and carnauba wax is 1:0.3:0.09.
[0065] The preparation method of modified glass fiber comprises the following steps: 0.8 kg of glass fiber is ultrasonically crushed for 20 minutes, then dispersed in 1.5 L of dilute sulfuric acid solution with a molar concentration of 2.5 mol / L, washed with water, mixed evenly with 0.2 kg of sodium dibutylnaphthalene sulfonate and 0.3 kg of pearl powder, and dried to obtain modified glass fiber.
[0066] Preparation Example 2-2
[0067] The difference from Preparation Example 2-1 is that in step (2), no modified glass fiber is added.
[0068] Preparation Example 2-3
[0069] The difference from Preparation Example 2-1 is that in step (2), carnabba wax is not added.
[0070] Preparation Example 2-4
[0071] The difference from Preparation Example 2-1 is that the mass ratio of clay, modified glass fiber and carnaba wax is 1:0.5:0.07.
[0072] Preparation Example 2-5
[0073] The difference from Preparation Example 2-1 is that the mass ratio of clay, modified glass fiber and carnaba wax is 1:0.1:0.2.
[0074] Preparation Example 2-6
[0075] The difference from Preparation Example 2-1 is that in the preparation method of the modified glass fiber, sodium dibutylnaphthalene sulfonate is not added.
[0076] Preparation Example 2-7
[0077] The difference from Preparation Example 2-1 is that pearlescent powder is not added in the preparation method of the modified glass fiber.
[0078] Example
[0079] Example 1
[0080] A two-component RTV adhesive sealing silicone rubber, comprising component A and component B, characterized in that component A comprises the following raw materials by weight: 100 kg of dimethyl silicone oil, 15 kg of modified filler, and 1 kg of chelated tin catalyst; component B comprises the following raw materials by weight: 100 kg of 107 silicone rubber, 10 kg of modified filler, 3 kg of crosslinking agent, and 3 kg of silane coupling agent kh550;
[0081] The modified filler comprises the following raw materials: 10 kg of modified white carbon black, 5 kg of nano calcium carbonate, 7 kg of modified clay and 2 kg of talcum powder.
[0082] The viscosity of dimethyl silicone oil is 10000 mPa·s, the viscosity of 107 silicone rubber is 10000 mPa·s, the chelated tin catalyst is purchased from Jinan Yuyi Chemical Co., Ltd., and the cross-linking agent is methyltriethoxysilane.
[0083] The preparation method of the modified filler comprises the following steps: dispersing the modified white carbon black in deionized water, stirring at a temperature of 65° C. for 25 minutes, adding nano calcium carbonate, modified clay and talcum powder, continuing stirring for 2 hours, grinding and drying to obtain the modified filler.
[0084] The preparation method of two-component RTV adhesive sealing silicone rubber comprises the following steps: dimethyl silicone oil and modified filler are stirred at a speed of 1000 rpm for 35 minutes under a vacuum degree of 0.1 MPa, a chelated tin catalyst is added and stirred for 1.5 hours to obtain component A;
[0085] 107 silicone rubber and modified filler were stirred at 1200 rpm for 30 min under a vacuum degree of 0.1 MPa, and a crosslinking agent and a silane coupling agent were added and stirred for 1.5 h to obtain component B;
[0086] Mix component A and component B in a mass ratio of 8:1 and cure to obtain the product.
[0087] The modified silica was prepared in Preparation Example 1-1, and the modified clay was prepared in Preparation Example 2-1.
[0088] Example 2
[0089] A two-component RTV adhesive sealing silicone rubber, which is different from Example 1 in that component A includes the following raw materials by weight: 100 kg of dimethyl silicone oil, 25 kg of modified filler, and 2 kg of chelated tin catalyst; component B includes the following raw materials by weight: 100 kg of 107 silicone rubber, 20 kg of modified filler, 5 kg of crosslinking agent, and 2 kg of silane coupling agent KH550;
[0090] The modified filler includes the following raw materials: 15 kg of modified white carbon black, 8 kg of nano calcium carbonate, 12 kg of modified clay, and 5 kg of talcum powder.
[0091] Example 3
[0092] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified white carbon black adopts Preparation Example 1-2.
[0093] Example 4
[0094] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified white carbon black adopts Preparation Example 1-3.
[0095] Example 5
[0096] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified white carbon black adopts Preparation Example 1-4.
[0097] Example 6
[0098] A two-component RTV bonding and sealing silicone rubber, which is different from Example 1 in that the modified white carbon black adopts Preparation Example 1-5.
[0099] Example 7
[0100] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified silica is prepared as in Preparation Example 1-6.
[0101] Example 8
[0102] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified white carbon black adopts Preparation Example 1-7.
[0103] Example 9
[0104] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified clay adopts Preparation Example 2-2.
[0105] Example 10
[0106] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified clay adopts Preparation Example 2-3.
[0107] Embodiment 11
[0108] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified clay adopts Preparation Example 2-4.
[0109] Example 12
[0110] A two-component RTV bonding and sealing silicone rubber, which is different from Example 1 in that the modified clay is prepared as in Preparation Example 2-5.
[0111] Embodiment 13
[0112] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified clay is prepared as in Preparation Example 2-6.
[0113] Embodiment 14
[0114] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that the modified clay is prepared as in Preparation Example 2-7.
[0115] Comparative Example
[0116] Comparative Example 1
[0117] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that modified white carbon black is not added.
[0118] Comparative Example 2
[0119] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that an equal amount of white carbon black is used to replace the modified white carbon black.
[0120] Comparative Example 3
[0121] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that modified clay is not added.
[0122] Comparative Example 4
[0123] A two-component RTV bonding and sealing silicone rubber, which differs from Example 1 in that an equal amount of clay is used to replace the modified clay.
[0124] Performance testing
[0125] The two-component RTV adhesive sealing silicone rubber prepared in Examples 1-14 and Comparative Examples 1-4 was subjected to performance testing;
[0126] The Shore hardness was tested according to GB / T531-1999; the elongation at break and tensile strength were tested according to GB / T528-1998; the tear strength was tested according to GB / T529-1991; the shear strength was tested according to GB / T7124; and the operation time was tested according to GB16776-2005. The test results are shown in Table 1.
[0127] Table 1 Test data of embodiments and comparative examples
[0128]
[0129] Combining the examples and the data in Table 1, it can be seen that the two-component RTV adhesive sealing silicone rubber prepared in Examples 1-2, Example 5, and Example 11 have good mechanical properties, hardness, and operation time. Among them, the operation time of Example 1 is 6 min, the hardness is 35, the elongation at break is 550%, the tensile strength is 5.9 MPa, the tear strength is 5.7 MPa, and the shear strength is 5.6 MPa, indicating that the various components in the present application cooperate with each other to improve the mechanical properties of the silicone rubber, while increasing the hardness, viscosity, mechanical strength, and wear resistance of the silicone rubber, and improving the structural stability of the system after curing.
[0130] In the preparation method of modified silica in Example 3, modified graphene is not added. As can be seen from Table 1, relative to Example 1, the operation time is 13 min, the hardness is 45, the elongation at break is 520%, the tensile strength is 4.4 MPa, the tear strength is 4.3 MPa, and the shear strength is 4.2 MPa, indicating that the modified graphene has high strength and high elasticity, can be loaded on the surface or pores of silica, improve the tensile strength, elongation at break and wear resistance of silica, and is subsequently applied to silicone rubber to improve the mechanical properties, weather resistance and service life of silicone rubber.
[0131] In the preparation method of modified silica in Example 4, chitosan solution is not sprayed. As can be seen from Table 1, relative to Example 1, the operation time is 10 min, the hardness is 40, the elongation at break is 530%, the tensile strength is 5.1 MPa, the tear strength is 5.0 MPa, and the shear strength is 4.9 MPa, indicating that the chitosan solution is sprayed on the surface of silica, so that the modified graphene and silica bonding is more stable, and the subsequent chitosan can also cross-link with silicone rubber to improve the mechanical strength of silicone rubber. The modified silica has better mechanical properties, wear resistance and stability, and the corresponding properties of silicone rubber are subsequently improved.
[0132] Example 6 changes the mass ratio of white carbon black, modified graphene and chitosan solution. It can be seen from Table 1 that, relative to Example 1, the elongation at break, tensile strength, tear strength and shear strength performance are significantly better than those of Examples 3-4, but worse than those of Examples 1-2, indicating that there is a synergistic effect between white carbon black, modified graphene and chitosan solution. The modified graphene is loaded on the surface and pores of white carbon black, and the chitosan solution makes the white carbon black and the modified graphene adhere tightly. The modified white carbon black has good tensile strength, elongation at break and wear resistance. The subsequent application in silicone rubber also improves the adhesion and durability of silicone rubber.
[0133] In the preparation method of modified graphene in Examples 7-8, nano silicon dioxide and sodium dodecylbenzene sulfonate are not added respectively. As can be seen from Table 1, relative to Example 1, the elongation at break, tensile strength, tear strength and shear strength performance are significantly better than those in Example 3, but worse than those in Examples 1-2, indicating that nano silicon dioxide has higher mechanical strength and wear resistance, can be loaded on the surface of graphene, improve the tensile strength, hardness and toughness of graphene, and sodium dodecylbenzene sulfonate is used as a surface modifier to help graphene and nano silicon dioxide disperse in the solution, prevent agglomeration, improve the mechanical properties and stability of the modified graphene, and subsequently improve the mechanical strength of the silicone rubber such as tensile strength, tear strength and wear resistance.
[0134] In the preparation method of modified clay in Example 9, modified glass fiber is not added. As can be seen from Table 1, relative to Example 1, the operation time is 12 min, the hardness is 44, the elongation at break is 523%, the tensile strength is 4.5 MPa, the tear strength is 4.4 MPa, and the shear strength is 4.3 MPa, indicating that the modified glass fiber has good heat resistance and high strength, can be loaded on the surface of ceramsite, improve the mechanical strength, toughness and wear resistance of ceramsite, and subsequently improve the corresponding properties of silicone rubber.
[0135] In the preparation method of modified clay in Example 10, carnauba wax is not added. As can be seen from Table 1, relative to Example 1, the operation time is 9 min, the hardness is 39, the elongation at break is 535%, the tensile strength is 5.2 MPa, the tear strength is 5.1 MPa, and the shear strength is 5.0 MPa, indicating that after the carnauba wax is dissolved, the pretreated ceramsite can be coated, so that the modified glass fiber and the ceramsite are closely bonded, and the performance stability of the modified clay is improved. The subsequent application in silicone rubber makes the various components in the silicone rubber mixed evenly, thereby improving the performance stability of the silicone rubber.
[0136] Example 12 changes the mass ratio of clay, modified glass fiber and carnauba wax. It can be seen from Table 1 that, relative to Example 1, the elongation at break, tensile strength, tear strength and shear strength performance are significantly better than those of Examples 9-10, but worse than those of Examples 1-2, indicating that the modified glass fiber has good heat resistance and high strength, can be loaded on the surface of ceramsite, improve the mechanical strength, toughness and wear resistance of the ceramsite, and the carnauba wax can coat the pretreated ceramsite after being dissolved, so that the modified glass fiber and ceramsite are tightly bonded, thereby improving the corresponding properties of the silicone rubber.
[0137] In the preparation method of the modified glass fiber of Examples 13-14, sodium dibutylnaphthalene sulfonate and pearl powder are not added respectively. As can be seen from Table 1, relative to Example 1, the elongation at break, tensile strength, tear strength and shear strength performance are significantly better than those of Example 9, but worse than those of Examples 1-2, indicating that sodium dibutylnaphthalene sulfonate is attached to the glass fiber to increase the dispersibility of the glass fiber in the liquid, and the pearl powder can be loaded on the surface of the glass fiber to increase the strength, toughness and durability of the glass fiber. Subsequently, it is applied to modified clay to improve the corresponding properties of the clay, and finally applied to silicone rubber to improve the oxidation resistance and durability of silicone rubber, while adjusting the rheology, curing speed and hardness of silicone rubber.
[0138] Comparative Example 1 does not add modified silica. As can be seen from Table 1, relative to Example 1, the operation time is 20 min, the hardness is 55, the elongation at break is 490%, the tensile strength is 2.7 MPa, the tear strength is 2.6 MPa, and the shear strength is 2.5 MPa, indicating that modified silica can improve the hardness, tensile strength, tear strength and wear resistance of silicone rubber, so that it has better mechanical properties after curing.
[0139] Comparative Example 3 does not add modified clay. As can be seen from Table 1, relative to Example 1, the operation time is 19 min, the hardness is 52, the elongation at break is 498%, the tensile strength is 3.2 MPa, the tear strength is 3.1 MPa, and the shear strength is 3.0 MPa, indicating that the modified clay can increase the volume of silicone rubber, increase the density and hardness of the material, increase the hardness, tensile strength and tear resistance of silicone rubber, and improve the heat resistance of silicone rubber.
[0140] Comparative Examples 2 and 4 are modified silica replaced by an equal amount of silica and modified clay replaced by an equal amount of clay, respectively. As can be seen from Table 1, relative to Example 1, the elongation at break, tensile strength, tear strength and shear strength are significantly worse than those of Examples 1-2, but better than Comparative Examples 1 and 3, indicating that the modified silica and clay in the present application have better mechanical properties, and are subsequently applied to silicone rubber to improve the corresponding properties of silicone rubber.
[0141] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A two-component RTV adhesive sealing silicone rubber, comprising component A and component B, characterized in that: The A component comprises the following raw materials in parts by weight: 100 parts of dimethyl silicone oil, 15-25 parts of modified filler, and 1-2 parts of chelated tin catalyst; the B component comprises the following raw materials in parts by weight: 100 parts of 107 silicone rubber, 10-20 parts of modified filler, 3-5 parts of crosslinking agent, and 2-3 parts of silane coupling agent; The modified filler comprises the following raw materials: 10-15 parts of modified white carbon black, 5-8 parts of nano calcium carbonate, 7-12 parts of modified clay, and 2-5 parts of talc; The preparation method of the modified white carbon black comprises the following steps: (1) Grind the white carbon black, then disperse it in an aqueous solution of a silane coupling agent, add acetic acid, stir for 1-2 hours, wash with water, and filter to obtain pretreated white carbon black; (2) dispersing the modified graphene in deionized water, adding the pretreated white carbon black in step (1), stirring at a temperature of 80-85° C. for 1-2 h, filtering, then spraying the chitosan solution, dispersing evenly, drying, and grinding to obtain modified white carbon black; The preparation method of modified graphene comprises the following steps: adding hydrogen peroxide and concentrated hydrochloric acid to graphene, stirring evenly, reacting for 1-1.5 hours, washing with water to obtain hydroxyl-modified graphene, then dispersing in deionized water, adding nano-silicon dioxide and sodium dodecylbenzene sulfonate, stirring for 1-2 hours, filtering, and drying to obtain modified graphene; The preparation method of the modified clay comprises the following steps: (1) Grind the clay, disperse it in a sodium hydroxide solution and soak it for 2-3 hours, wash it with water, then disperse it in deionized water, add boric acid, stir it evenly, filter it, and obtain pretreated ceramsite; (2) dispersing the pretreated ceramsite of step (1) in anhydrous ethanol, adding modified glass fiber and carnauba wax, stirring at a temperature of 80-85° C. for 3-5 minutes, dispersing evenly, drying, and grinding to obtain modified clay; The preparation method of the modified glass fiber comprises the following steps: ultrasonically crushing the glass fiber for 15-20 minutes, dispersing it in a dilute sulfuric acid solution, washing it with water, mixing it evenly with sodium dibutylnaphthalene sulfonate and pearl powder, and drying it to obtain the modified glass fiber.
2. A two-component RTV adhesive sealing silicone rubber according to claim 1, characterized in that: The mass ratio of the white carbon black, the modified graphene and the chitosan solution is 1:0.1-0.3:0.5-0.
7.
3. A two-component RTV adhesive sealing silicone rubber according to claim 1, characterized in that: The mass ratio of the pottery clay, the modified glass fiber and the carnauba wax is 1:0.3-0.5:0.07-0.
09.
4. A two-component RTV adhesive sealing silicone rubber according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: dispersing modified white carbon black in deionized water, stirring at a temperature of 60-65° C. for 20-25 minutes, adding nano calcium carbonate, modified clay and talcum powder, continuing stirring for 1-2 hours, grinding and drying to obtain the modified filler.
5. The method for preparing a two-component RTV adhesive sealing silicone rubber according to claim 1, characterized in that: The method comprises the following steps: stirring dimethyl silicone oil and modified filler at a vacuum degree of 0.1-0.1 MPa at a speed of 900-1000 rpm for 30-35 minutes, adding a chelated tin catalyst and continuing stirring for 1-1.5 hours to obtain component A; Stir 107 silicone rubber and modified filler at a vacuum degree of 0.1-0.1 MPa at a speed of 1100-1200 rpm for 20-30 min, add a crosslinking agent and a silane coupling agent and continue stirring for 1-1.5 hours to obtain component B; Mix component A and component B in a mass ratio of 5-10:1 and cure to obtain the product.
Citation Information
Patent Citations
Preparation method of environment-friendly tire tread rubber
CN110066438A
Water-permeable mortar for pavement brick laying
CN110171946A